2009
DOI: 10.1007/s11695-009-9937-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 11β-Hydroxysteroid Dehydrogenase Type 1 in Hepatic and Visceral Adipose Tissue is Associated with Metabolic Disorders in Morbidly Obese Patients

Abstract: 11beta-HSD1 expression is higher in liver in comparison to adipose tissue in obese patients. The observed correlations between hepatic and VAT 11beta-HSD1 expression with dyslipidemia and insulin resistance suggest that this enzyme might have a pathogenic role in obesity and related metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 49 publications
8
42
2
2
Order By: Relevance
“…The results are conflicting when comparing HSD11B1 mRNA levels in the adipose tissue and liver of obese patients with or without MetS. In contrast to our results, Baudrand et al (13) did not find differences in HSD11B1 expression between obese subjects with and without MetS, while Torrecilla et al (35) observed higher mRNA levels of HSD11B1 in the liver of patients with MetS. Nevertheless, this particular finding of ours is in line with previous studies, in animal models and more particularly in transgenic mice, where overexpression of the HSD11B1 selectively in adipose tissue led to full MetS, with visceral obesity, hypertension, dyslipidaemia and IR (14).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 99%
See 2 more Smart Citations
“…The results are conflicting when comparing HSD11B1 mRNA levels in the adipose tissue and liver of obese patients with or without MetS. In contrast to our results, Baudrand et al (13) did not find differences in HSD11B1 expression between obese subjects with and without MetS, while Torrecilla et al (35) observed higher mRNA levels of HSD11B1 in the liver of patients with MetS. Nevertheless, this particular finding of ours is in line with previous studies, in animal models and more particularly in transgenic mice, where overexpression of the HSD11B1 selectively in adipose tissue led to full MetS, with visceral obesity, hypertension, dyslipidaemia and IR (14).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 99%
“…Independently of the MetS presence, the HSD11B1 mRNA levels were significantly higher in the liver than in SAT and VAT, a finding consistent with another study (13). This dominant expression of HSD11B1 in the liver may serve the important role of glucocorticoids in the regulation of gluconeogenic enzymes, hepatic glucose production and glycogen stores (27,28).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…11b-HSD1 null mice exhibited decreased white adipose depot, resistance to hyperglycemia induced by fat feeding, and increased hepatic insulin sensitivity (Alberts et al 2002, 2003, Kershaw et al 2005, Stewart & Tomlinson 2009. By contrast, increased 11b-HSD1 activity in WAT resulted in the development of visceral adiposity, hyperglycemia, and insulin resistance in morbidly obese patients (Kannisto et al 2004, Baudrand et al 2010. Moreover, our previous studies suggested that 11b-HSD1 could promote differentiation of white adipocyte in vitro (Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the 11βHSD1 gene in mice is associated with enhanced adipocyte differentiation and higher adipose tissue mass [2]. Increased 11βHSD1 gene expression has also been found in the adipose tissue of obese Zucker rats [3] and in the adipose tissue of morbidly obese patients [4][5][6][7][8]. It has been postulated that increased activation of glucocorticosteroids in adipose tissue (due to increased 11βHSD1 activity) plays an important role in the development of central obesity and metabolic syndrome [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%